Provenance trials of stone pine (Pinus pinea L.) in the Aegean region: tenth year evaluation - Acar F.C.; Altun Z.G.; Boza A.; Bilgin F. (Mediterranean stone pine for agroforestry, 2013)
The purpose of the project here analysed was the establishment of provenance trials in natural environment of stone pines in order to determine adaptation ability and growth performance as well as to conserve gene materials of various origins in ex-situ environments. This project has been simultaneously implemented in France, Italy, Spain, Tunisia, Morocco and Turkey under the coordination of FAO-INRA. A total of 26 origins have been used in the trial with three replications in Kozak and Yigintas plots of the Aegean Region of Turkey. Spacing for the saplings was 6 × 6 m at both of the plots. Because no significant differences were found at the statistical analysis of 5th year data, here the collected data after 10 years were analyzed and evaluated. According to the variance analysis, significant differences were found between the provenances in terms of mean height (p value 0.1 %), mean diameter (0.5 %) and mean number of conelets (0.1 %). However, there were not any significant differences among the crown diameters and the survival ratios. There were significant differences between the trial plots. The reasons of the differences between two trial plots might be the distance to the sea, bedrock type and soil depth. For more precise evaluation of the provenance trials, the tree age should be minimum 20 years, therefore we should wait for results from next decade.
AGROPINE 2011 International Meeting on Mediterranean Stone Pine for Agroforestery, 2011/11/17-19, Valladolid (Spain)